10(c-2)+5=3+c-18

Simple and best practice solution for 10(c-2)+5=3+c-18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10(c-2)+5=3+c-18 equation:


Simplifying
10(c + -2) + 5 = 3 + c + -18

Reorder the terms:
10(-2 + c) + 5 = 3 + c + -18
(-2 * 10 + c * 10) + 5 = 3 + c + -18
(-20 + 10c) + 5 = 3 + c + -18

Reorder the terms:
-20 + 5 + 10c = 3 + c + -18

Combine like terms: -20 + 5 = -15
-15 + 10c = 3 + c + -18

Reorder the terms:
-15 + 10c = 3 + -18 + c

Combine like terms: 3 + -18 = -15
-15 + 10c = -15 + c

Add '15' to each side of the equation.
-15 + 15 + 10c = -15 + 15 + c

Combine like terms: -15 + 15 = 0
0 + 10c = -15 + 15 + c
10c = -15 + 15 + c

Combine like terms: -15 + 15 = 0
10c = 0 + c
10c = c

Solving
10c = c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-1c' to each side of the equation.
10c + -1c = c + -1c

Combine like terms: 10c + -1c = 9c
9c = c + -1c

Combine like terms: c + -1c = 0
9c = 0

Divide each side by '9'.
c = 0

Simplifying
c = 0

See similar equations:

| 124-9w=3 | | 5x-4=2(x-2)+3x | | 12y-5y=15 | | x^2-1.5x+.5625=0 | | 1.3x+2.3=0.6x-4.07 | | -9c=8-10c | | 9a+2b+8a-3b= | | 2a+6y=2 | | 3+p=15 | | -3n=-4n+7 | | 6x-3=15x-15 | | 18x^2+73x-36=0 | | 36x^2-5=95 | | 2x+1=-31 | | 1-x-x=-9 | | x-5+3=-2 | | -2u-7=-3u | | 3.14r^2=225(3.14) | | 8x^2+6x-65=0 | | [h]-4=9 | | -2.8m+7-0.2m=-0.8-3m+7.8 | | 8a*x=414 | | x-5+=-2 | | 3v+16=67 | | 24x^2-16=16 | | 6v^2+46v+60=0 | | 3r-2r+r-3ab= | | 18x^2-19x+216=0 | | 5y-16= | | 35x^2+3x-20=0 | | 28n^4+16n^3-80n= | | 3r-16=r-8 |

Equations solver categories